Effects of Health Education on Food Safety Cognitions Among Pregnant Mothers in Primary Healthcare Institutions in Rivers State, Nigeria - Ibara, Augustina Ngozi; Ekenedo, Obiageri (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
Abstract This study investigated the effects of health education on attitudes and behavioural intentions towards food safety cognitions among pregnant mothers attending primary healthcare institutions in Rivers State. A pre-test and post-test design was adopted with a population which consisted of 1,838,789 pregnant mothers attending primary healthcare institutions in Rivers State. A sample size of 270 was selected using a multistage sampling procedure. Data was collected using a structured test instrument with a reliability index of 0.78. Data collected were analyzed with the aid of the Statistical Product for Service Solution (SPSS V-23) using mean, standard deviation (SD) and One-Way Analysis of Covariance (ANCOVA) at 0.05 level of significance. The findings of the study revealed that health education had a positive effect on food safety cognitions among pregnant mothers in Rivers State. The result of the ANCOVA showed that the intervention had a significant effect [F(1,49) = 2.69, p<0.05] on food safety cognition. However, only 5.3% (ω2 = 0.053) of the variance in the post-test cognition scores could be explained by the intervention. It was concluded that health education is an effective strategy to influence pregnant mothers’ food safety cognition, which is necessary to prevent them and their babies from food-borne diseases or food poisoning. It was recommended among others that, nurses, and other healthcare workers in the primary healthcare facilities should routinely educate pregnant mothers on food safety to increase awareness of food safety; and the government should enforce food safety by encouraging health workers to visit pregnant mothers’ home from time to time for assessment, with special focus on hygienic kitchen environment which promotes food safety; and to ensure food safety is maintained.